Research progress of vascularization strategies of tissue-engineered bone - Lv, Nanning; Zhou, Zhangzhe; Hou, Mingzhuang; Hong, Lihui; Li, Hongye; Qian, Zhonglai; Gao, Xuzhu; Liu, Mingming (Frontiers in Bioengineering and Biotechnology, 2024)
The bone defect caused by fracture, bone tumor, infection, and other causes is not only a problematic point in clinical treatment but also one of the hot issues in current research. The development of bone tissue engineering provides a new way to repair bone defects. Many animal experimental and rising clinical application studies have shown their excellent application prospects. The construction of rapid vascularization of tissue-engineered bone is the main bottleneck and critical factor in repairing bone defects. The rapid establishment of vascular networks early after biomaterial implantation can provide sufficient nutrients and transport metabolites.If the slow formation of the local vascular network results in a lack of blood supply, the osteogenesis process will be delayed or even unable to form new bone. The researchers modified the scaffold material by changing the physical and chemical properties of the scaffold material, loading the growth factor sustained release system, and combining it with trace elements so that it can promote early angiogenesis in the process of induced bone regeneration, which is beneficial to the whole process of bone regeneration. This article reviews the local vascular microenvironment in the process of bone defect repair and the current methods of improving scaffold materials and promoting vascularization.